2014
DOI: 10.1007/s00432-014-1824-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the novel Wnt receptor ROR2 is increased in breast cancer and may regulate both β-catenin dependent and independent Wnt signalling

Abstract: This is the first study to report the expression of ROR2 in breast cancer. Breast cancer patients expressing ROR2 had a significantly worse prognosis than those lacking ROR2. ROR2 may regulate both β-catenin-dependent and β-catenin-independent Wnt signalling pathways, and represents a potential diagnostic and therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 18 publications
6
66
2
Order By: Relevance
“…gbx2 is a direct target gene (Li et al, 2009) and ap2alpha is one of the immediate early Wnt/β-catenin responsive genes at the neural plate border (de Crozé et al, 2011). Although Ror2 is a major receptor in β-catenin-independent Wnt signaling, it has also been reported that Ror2 can positively or negatively regulate Wnt/β-catenin signaling depending on the cellular context (Billiard et al, 2005;Green et al, 2007;Henry et al, 2015;Li et al, 2008;Mikels et al, 2009;Mikels and Nusse, 2006;Rasmussen et al, 2013). However, we found that neither lowering nor increasing Wnt/β-catenin activity by overexpression of dnLef or Tcf1, respectively, rescued NPB specification in Ror2-depleted embryos.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…gbx2 is a direct target gene (Li et al, 2009) and ap2alpha is one of the immediate early Wnt/β-catenin responsive genes at the neural plate border (de Crozé et al, 2011). Although Ror2 is a major receptor in β-catenin-independent Wnt signaling, it has also been reported that Ror2 can positively or negatively regulate Wnt/β-catenin signaling depending on the cellular context (Billiard et al, 2005;Green et al, 2007;Henry et al, 2015;Li et al, 2008;Mikels et al, 2009;Mikels and Nusse, 2006;Rasmussen et al, 2013). However, we found that neither lowering nor increasing Wnt/β-catenin activity by overexpression of dnLef or Tcf1, respectively, rescued NPB specification in Ror2-depleted embryos.…”
Section: Discussioncontrasting
confidence: 82%
“…Ror2 has been shown to modulate Wnt/β-catenin signaling and interestingly, both positive and negative regulation of the Wnt/β-catenin pathway has been reported (Billiard et al, 2005;Green et al, 2007;Henry et al, 2015;Li et al, 2008;Mikels and Nusse, 2006;Rasmussen et al, 2013). However, neither inhibition nor activation of Wnt/β-catenin signaling by co-injection of effective doses of dominant-negative (dn)lef1 RNA or tcf1 RNA with Ror2 MO, respectively, rescued the downregulation of msx1 ( Fig.…”
Section: Ror2 Is Required For Neural Crest Induction and Specificatiomentioning
confidence: 90%
“…In the lung cancer, an aberrant expression and/or alteration of the Wnt signaling components also are observed in 50% of human NSCLC cell lines and lung cancer resected samples [42], in which Wnt signaling is associated with increased proliferation and metastatic properties of lung cancer cells, poor prognosis, and resistances to conventional chemoradiotherapies and targeted therapies in lung cancer patients [14, 33, 4345]. Of interest, implications of dysregulated noncanonical Wnt signaling and the cancer type-dependent oncogenic or tumor suppressor role of Wnt signaling in tumorigenesis have recently spurred an increasing attention in the metastasis and therapeutic resistances of lung cancer [14, 22, 23, 25, 31, 36, 4547]. …”
Section: Discussionmentioning
confidence: 99%
“…However, a constitutive expression or increased expression of Wnt5a and its receptor Ror2 is involved in enhanced invasive and metastatic properties of many cancer types, suggesting an oncogenic role of Wnt5a/Ror2 signaling in tumorigenesis [17, 21, 40, 5154]. In addition to its oncogenic roles in cancers, Wnt5a also has been found to inhibit canonical Wnt/ β -catenin signaling in a Ror2-dependent manner and has a tumor suppressor role in several cancer types, such as colorectal cancer (CRC) [55], thyroid cancer [56], and maybe breast cancers as well [34, 36, 57]. With respect to its antitumor activity, Wnt5a is able to inhibit tumor invasion and metastasis by antagonizing the Wnt/ β -catenin signaling pathway and inducing the degradation of β -catenin [32].…”
Section: Discussionmentioning
confidence: 99%
“…Yes (19,127,132) Yes (48,133) Breast cancer (81) ; prostate cancer (41) ; melanoma (90,92) ; non-small cell lung cancer (134) ; colorectal cancer (135) ; gastric cancer (136) ; ovarian cancer (131) …”
Section: Ror2mentioning
confidence: 99%